Treatment of Fever in Children - S.A. Kramarev (Zaslavsky O.Yu., 2012)
The lecture details the etiology, pathogenesis and treatment strategy in fever in children. Attention is paid to clinical researches on the effectiveness of paracetamol and ibuprofen - the most popular antipyretics in pediatric practice.